Post-transplant lymphoproliferative disease and other malignancies after pediatric cardiac transplantation. Issue 5 (October 2015) - Haynes, Susan E.; Saini, Shermini; Schowengerdt, Kenneth O.
<x xml:space="preserve">Abstract</x> Purpose of review Post-transplant lymphoproliferative disorders (PTLDs) remain a significant cause of morbidity and mortality after pediatric solid organ transplantation (SOT). PTLD treatment outcomes have improved steadily over the past decade, in large part due to an enhanced understanding of the disease process, newer immunosuppression regimens, and implementation of evolving chemotherapeutic treatment protocols. Recent findings New therapies continue to be employed to treat PTLDs while maintaining normal allograft function in SOT recipients. These include use of immunosuppressant medications with antitumor activity (mammalian target of rapamycin inhibitors), monoclonal antibody therapies, and the advent of cytotoxic T-cell therapy. Treatment methods to render latent Epstein–Barr virus (EBV)-infected tumor cells more susceptible to antiviral agents continue to be investigated. Summary PTLD remains a significant potential complication after SOT, particularly in pediatric patients who are more likely to be EBV-negative at the time of transplant and subsequently undergo EBV seroconversion. Risk for PTLD may be reduced by employing strategies such as EBV prophylaxis in seronegative patients, minimizing overall intensity of immunosuppression, and utilizing newer agents that have both immunosuppressive and antiproliferative properties. Treatment outcomes for PTLD have steadily improved over the past decade, related in part to the availability of monoclonal antibody therapies and refined chemotherapeutic regimens.